Pengaruh Promosi dan Harga Terhadap Keputusan Nasabah dalam Memilih Cicilan Emas di PT Pegadaian Syariah Jelutung Jambi - Ferdi Agustiar Syarmaheza; Putri Apria Ningsih; Ogi Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Gold is a relatively stable investment instrument that is highly favored by the public including through gold installment products offered by Islamic financial institutions. This product provides easier access to gold ownership through a gradual payment system. However, the high level of public interest in this product does not always translate into actual purchasing decisions, as customer decisions are influenced by various factors, particularly promotion and price. Therefore, this study aims to analyze the influence of promotion and price on customers’ decisions in choosing gold installment products at PT Pegadaian Syariah Jelutung Jambi. This research employs a quantitative approach using a questionnaire distributed to 81 respondents selected through purposive sampling. The collected data were analyzed using multiple linear regression. The results of the study indicate that promotion and price have a positive and significant effect on customers’ decisions, both partially and simultaneously. The coefficient of determination (R²) of 65.8% shows that these two variables can explain 65.8% of the variation in customer decisions, while the remaining 34.2% is influenced by other factors outside the research variables. Thus, promotion and price are proven to be important factors in determining customers’ decisions in choosing gold installment products at PT Pegadaian Syariah Jelutung Jambi. The findings of this study are expected to serve as a consideration for the company in developing more effective marketing strategies.